Case Study: Efektivitas Neuro Develomental treatment Pada Cerebral Palsy spastic Diplegia - Ghulam Fahima Primadasa; Agus Widodo (Jurnal Kesehatan dan Fisioterapi, 2022)
Cerebral palsy CP is a permanent disorder that affects the development of movement and causes activity limitations. The prevalence in 2016 the increase in CP sufferers in the world reached 2.6-2.7 out of 1000 of live births in the world. Meanwhile in Indonesia, according to BPS RI in 2012, the number of CP children in Indonesia reached 532,130 children. Clinical observations show that Neurodevelopmental treatment exercises in children with CP diplegia show good results. But research is still limited to support this, therefore this case study aims to see the effectiveness of Neuro Developmental Treatment which includes children with Spastic Diplegia CP. In this study, the author uses the case study method, namely by taking individual samples and providing training programs directly to respondents with CP conditions at PKU Muhamadiyah Sukoharjo Hospital with the concept of Neurodevelopmental treatment training. The research was conducted 7 times. The treatment given is Neuro Development Treatment which includes Handling, facilitation, inhibition, and key point of control, then for the outcome.Keywords: Cerebral palsy Spastik Diplegi, Neurodevelopmental Treatment, NDT, Treatment for CP Spastik diplegia, Case Study